ANALISIS KUALITAS KONSTRUKSI PERUMAHAN REAL ESTATE DI KOTA BENGKULU BERDASARKAN PERSEPSI KONSUMEN DAN KESESUAIAN PERSYARATAN TAHAN GEMPA - Meilia Evita; Fepy Supriani (Universitas Bengkulu, 2019)
This research aims to know the quality of real estate construction according to consumers’ perception and compatibility of requirement. The requirement used in this research is the Technical Guidelines of Earthquake-Resistant House and Building. Besides, according to consumers’ perception, it can elaborate the main priority of the increasing quality of developer’s performance. The research used survey methods. They were field observation, interview, and distributing 146 questionnaires which take sample in six real estate residences in Bengkulu. The questionnaire was analyzed using frequency distribution method, mean and rank, and importance-performance. The result of analysis elaborated that the construction quality of real estate residence according to consumers’ perception is quite good with percentage 65, 147%. The priority indicators to increase the performance of real estate developer are the quality of floor, wall, frame, door, and window. On the other hand, the quality of real estate residence according to working compatibility with earthquake-resistant requirement, it is quite good with percentage 64,236% and compatibility of material with earthquake resistant requirement is in good quality with percentage 94,639%.